A mask to modify inspired air temperature and humidity and its effect on exercise induced asthma. Issue 6 (June 1992) - Nisar, M; Spence, D P; West, D; Haycock, J; Jones, Y; Walshaw, M J; Earis, J E; Calverley, P M; Pearson, M G
Abstract : BACKGROUND: Heat and moisture loss from the respiratory tract during exercise are important triggers of exercise induced asthma. METHODS: A new heat and moisture exchange mask has been developed which both recovers exhaled heat and water and has a sufficiently low resistance for use during exercise. The effect of the mask on inspired air temperature was studied in four normal subjects. Eight asthmatic subjects performed identical exercise protocols on three separate days, breathing room air through a conventional mouthpiece, a dummy mask, and the new heat and moisture exchange mask. Seven different asthmatic subjects exercised while breathing cold air at -13 degrees C through a dummy or active mask. RESULTS: All subjects found the new mask comfortable to wear. The mean inspired temperature when the mask was used rose to 32.5 (1.4) degrees C when normal subjects breathed room air at 24 degrees C and to 19.1 (2.7) degrees C when they inhaled subfreezing air at -13 degrees C. The heat and moisture exchange mask significantly reduced the median fall in forced expiratory volume in one second (FEV1) after exercise to 13% (range 0-49%) when asthmatic subjects breathed room air compared with 33% (10-65%) with the dummy mask and 28% (21-70%) with the mouthpiece. The fall in FEV1 when the asthmatic subjects breathed cold air was 10% (0-26%) with the heat and moisture exchange mask compared with 22% (13-51%) with the dummy mask. CONCLUSION: Use of a heat and moisture exchange mask can raise the inspired temperature and humidity and ameliorate the severity of exercise induced asthma. The mask may be of practical value in non-contact sport or for people working in subzero temperatures.